Foreign Language Learning Practices by High School Seniors in the Context of Modernization of Foreign Language School Education (2020–2024) - Obraztsov, Igor V.; Polovnyov, Andrey V. (Voprosy obrazovaniâ, 2025)
The purpose of the article is to analyze informal additional foreign language learning practices used by high school seniors in the context of modernization of school foreign language education, primarily expressed in optimizing the requirements for the formation of a multilingual component and the loss of the status of a compulsory subject in a second foreign language. The research strategy involves a comparative analysis between two reference points: 2020 and 2024, using data from official statistics, such as the Federal State Statistics Service (Rosstat) and specifically conducted sociological research by the MSLU sociological laboratory in cooperation with the NAFI research company among students of grades 8-11 in the Moscow region and other regions of the Russian Federation. Additionally, the study focuses on the informal (extracurricular) learning practices of seniors for foreign languages. The obtained results indicate an increase in the proportion of English language learners with a simultaneous loss of the role and importance of the traditional German and French languages for Russian foreign language education, as well as a reduction in the study of other foreign languages. The ongoing public discussions about the reorientation of the foreign component of school education in accordance with the new geopolitical situation to the languages of Asia and Africa do not have any real opportunities for their implementation due to the lack of staff and logistical support. At the same time, the maintenance of the elite segment of foreign language education in the form of specialized educational institutions with in-depth study of foreign languages is fixed, which does not eliminate, but rather perpetuates the gap in unequal access to opportunities for obtaining foreign language competencies and career opportunities. Additional (extracurricular) foreign language classes, including paid ones, continue to be in demand among seniors. The degree of involvement of schoolchildren in additional educational practices is determined by regional, settlement and professionally oriented factors.